Penguatan Edukasi Bahasa Indonesia sebagai Strategi Pencegahan Bullying dalam Mendukung Tujuan Pembangunan Berkelanjutan (SDGS) di SDN 02 Simalanggang - Indra Yeni; Latifah Qorimahtul Fajri; Annisa Nur Fahada; Gusridur Yanti; Idris Albasyitu; Dini Aminarti (Universitas Palangka Raya, 2025)
The activity of strengthening Indonesian language education as a bullying prevention strategy at SDN 02 Simalanggang aims to raise students' awareness of the negative impacts of bullying and the importance of good communication in creating positive relationships, in line with the Sustainable Development Goals (SDGs), particularly SDG 4, which focuses on quality education. This program was carried out on June 20, 2025, involving 200 students and 15 teachers. The methods used include observation, socialization, effective communication training, and counseling for students involved in bullying cases. The results of the activity show a significant increase in students' understanding of bullying and the importance of speaking properly, as well as a 30% reduction in bullying incidents at school. Evaluation was carried out through direct observation, which showed positive changes in students' behavior, both as perpetrators and victims of bullying. This program also reinforces the concepts of effective communication and character education, which have proven to reduce bullying and create a safer and more inclusive learning environment. Based on these results, the activity provides great benefits for students' character development and creates a more supportive school atmosphere, contributing to the achievement of SDGs in quality education. The program involved a series of activities, such as observation to identify bullying incidents, socialization sessions to inform students about bullying and its consequences, and communication training to improve students' skills in handling conflicts constructively. Counseling was also provided to students who were either perpetrators or victims of bullying, helping them to understand the impact of their actions and how to manage emotions and behavior in a more positive manner. After the program, a noticeable shift in behavior was observed, particularly in the way students interacted with one another. A significant reduction in bullying incidents by 30% demonstrates the effectiveness of communication-based interventions.